Islamic Education Teacher's Strategy in Implementing Merdeka Curriculum at SMP Negeri 16 Semarang - Nimatal Maula, Nely; Muthohar, Sofa; Fihris (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The Merdeka curriculum emphasizes the importance of student independence and courage in the learning process, providing space for teachers to develop strategies that suit the needs of each student. The implementation of this curriculum is highly dependent on the innovations made by teachers in designing effective learning strategies. This study aims to determine how the PAI teacher's strategy in implementing the Merdeka Curriculum at SMP Negeri 16 Semarang. This research uses a descriptive qualitative method with data collection techniques through observation, interviews and documentation. The results of this study show that the PAI teacher's strategy in implementing the Merdeka Curriculum at SMP Negeri 16 Semarang is carried out in several ways, namely, collaborative learning strategies, Problem Based Learning and Project Based Learning strategies, and technology utilization strategies in the learning process.